Network Effects: Betwixt and Between - Mohammed Mardan; Mark J. Tremblay (Center for Economic Studies and ifo Institute (CESifo), 2022)
We challenge the dichotomy of network effects and highlight that they are not an exogenous characteristic of networks, but endogenous to the decisions of network users. When users choose which activities to perform in a network, multi-activity users transform indirect into direct network effects and a network effectively becomes one-sided if merely multi-activity users frequent it. Our work contributes to theory by determining the underlying micro-foundations that produce what the literature calls a two-sided market and by highlighting how the standard two-sided pricing results arises only under very specific conditions. We also contribute to estimation by illustrating how the presence of multi-active users can challenge identification in network industries.
Keywords: L10; L20; D21; D42; 330; platforms; one-sided markets; two-sided markets; multi-siding users